THE INFLUENCE OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE WORK PRODUCTIVITY - Simanjuntak, Demak Claudia Yosephine; Panggabean, Esther Praja Anggriany; Ahmadi, Edy Anas (IJOSMAS, 2023)
The Study This aim For test influence discipline work and work environment to productivity Work employee. Type research used _ is study quantitative . Study This use method census , that is take all population become respondent research . Amount respondent is 30 people. Processing and analysis techniques data, test validity, reliability test, assumption test classic , analysis , analysis multiple linear regression , and analysis of hypothesis testing (t test, f test, and coefficients determination ). Research results show that individually and individually together environment work and discipline Work influential to productivity Work CV Mutuara Jaya employees. Environment comfortable and level work discipline high work will increase productivity Work employee